In Space No One Can Hear You Speak: Embodied Language in Stanisław Lem's Solaris and Peter Watts's Blindsight. Issue 3 (2015) - Kowalewski, Hubert
Abstract : The article explores the depictions of communication with extraterrestrial life-forms from the point of view of cognitive linguistics and the philosophy of embodied realism. Optimism in visions of Contact, i.e. the degree to which communication is presented as possible and relatively easy, often results from ignoring the embodied nature of the human mind and language. Two novels analyzed in this article, Stanisław Lem's Solaris (2003 [1961]) and Peter Watts's Blindsight (2006), paint a more pessimistic picture of interstellar communication. To a large extent, this pessimism results from greater awareness of the problems related to embodiment of the mind and language.